Visualisasi Karakter Profetik dalam Diri Akuntan Pendidik - Gemelthree Ardiatus Subekti; Hamidah -; Astuti Dola Bastina (Jurusan Akuntansi Politeknik Negeri Malang, 2020)
This research aims to contribute for an educator accountant in carrying out his profession by imitating and emulating the characters that already exist in the Prophet Muhammad. The approach in the formulation of thought uses a literature study by comparing the character of the Prophet Muhammad and the accountant educators who have unethichal behaviors. From these comparisons, the researcher gives an argument about why accountants educators should imitate and emulate the character of the Prophet Muhammad in carrying out their duties. The essence of ethical matters is fundamental in accounting, especially in the context of developing and enhancing the role of the teaching accountant profession in order to be able to act professionally. Abstrak Penelitian ini bertujuan mampu memberikan kontribusi bagi seorang akuntan pendidik dalam menjalankan profesinya dengan mencontoh dan meneladani karakter yang telah ada dalam diri Nabi Muhammad SAW. Pendekatan dalam perumusan pemikiran ini menggunakan studi kepustakaan dengan membandingkan antara karakter Nabi Muhammad SAW dengan oknum akuntan pendidik yang berperilaku tidak etis. Dari perbandingan tersebut peneliti memberikan argumen mengapa akuntan pendidik harus mencontoh dan meneladani karakter Nabi Muhammad SAW dalam menjalankan tugasnya. Esensi perihal etis sangat penting dalam akuntansi terutama dalam rangka pengembangan dan peningkatan peran profesi akuntan pendidik untuk dapat bertindak secara profesional.